Clinical whole exome sequencing from dried blood spot identifies novel genetic defect underlying asparagine synthetase deficiency. Issue 1 (15th December 2017) - Abhyankar, Avinash; Lamendola‐Essel, Michelle; Brennan, Kelly; Giordano, Jessica L.; Esteves, Cecilia; Felice, Vanessa; Wapner, Ronald; Jobanputra, Vaidehi
Key Clinical Message: We add two novel variants to the existing mutation spectrum of ASNS gene. Loss of ASNS function should be suspected in newborns presenting with congenital microcephaly, intellectual disability, progressive cerebral atrophy, and intractable seizures. Acquisition and sequencing of stored newborn blood spot can be a valuable option when no biological samples are available from a deceased child. Abstract : We add two novel variants to the existing mutation spectrum of ASNS gene. Loss of ASNS function should be suspected in newborns presenting with congenital microcephaly, intellectual disability, progressive cerebral atrophy, and intractable seizures. Acquisition and sequencing of stored newborn blood spot can be a valuable option when no biological samples are available from a deceased child.